Disease Risk Assessments Involving Companion Animals: an Overview for 15 Selected Pathogens Taking a European Perspective. (July 2016) - Rijks, J.M.; Cito, F.; Cunningham, A.A.; Rantsios, A.T.; Giovannini, A.
Summary: Prioritization of companion animal transmissible diseases was performed by theC ompanionA nimals multisectoriaL interprofessionaL I nterdisciplinaryS trategicT hink tankO n zoonoses (CALLISTO) project. The project considered diseases occurring in domesticated species commonly kept as pets, such as dogs and cats, but also included diseases occurring in captive wild animals and production animal species. The prioritization process led to the selection of 15 diseases of prime public health relevance, agricultural economic importance, or both. An analysis was made of the current knowledge on the risk of occurrence and transmission of these diseases among companion animals, and from companion animals to man (zoonoses) or to livestock. The literature was scanned for risk assessments for these diseases. Studies were classified as import risk assessments (IRAs) or risk factor analyses (RFAs) in endemic areas. For those pathogens that are absent from Europe, only IRAs were considered; for pathogens present throughout Europe, only RFAs were considered. IRAs were identified for seven of the eight diseases totally or partially absent from Europe. IRAs for classical rabies and alveolar echinococcosis found an increased risk for introduction of the pathogen into officially disease-free areas as a consequence of abandoning national rules and adopting the harmonized EU rules for pet travel. IRAs for leishmaniosis focused on risk associated with the presence of persistently infected dogs in new geographical areas, taking into consideration the risk of disease establishment should a competent vector arise. IRAs for Crimean–Congo haemorrhagic fever and West Nile fever indicated that the likelihood of introduction via companion animals was low. IRAs for bluetongue paid no attention to the risk of introduction via companion animals, which was also the case for IRAs for foot-and-mouth disease, the only disease considered to be absent from Europe. RFAs dealing with the risk factors for companion animals to become infected were identified for eight of the 14 diseases found in Europe or parts of it. RFAs for leptospirosis were most numerous (four studies). The host related risk factor 'age' was identified as significant for dogs in at least two RFAs for cystic echinococcosis and giardiasis. Among husbandry and healthcare related factors, 'eating (uncooked) offal', 'being free roaming' and 'poor deworming practice' were associated with risk for dogs in at least two RFAs for cystic echinococcosis, while 'having received recent veterinary treatment' was identified as a risk factor in at least two studies on infection with extended spectrum beta lactamase-producing bacteria, one in horses and the other in dogs and cats. Finally, although the environmental factors 'season' and 'hydrological density' were identified as significant risk factors for dogs in at least two RFAs for leptospirosis, the inconsistent case definitions used in those studies made comparison of study results problematic. RFAs considering the risk of people becoming infected from companion animals were identified for eight of the 14 diseases found in Europe or parts of it. RFAs for human campylobacteriosis were the most numerous ( n = 6). Most studies made an assessment as to whether keeping a pet per se, or keeping a pet with supposed or known risk factors, was a risk factor for people relative to other risks. This allowed some studies to report the population attributable risk or population attributable fraction of the incidence of human disease due to companion animals (for campylobacteriosis, salmonellosis and toxoplasmosis), which is a measure that is easy to perceive for laymen and policy makers. No RFAs were found that dealt with the risk to food animals from companion animals for any of the 15 pathogens investigated. Few risk method-based studies were identified that provided information on risk factors for companion animals and on their role as a source of these 15 selected diseases, indicating a clear knowledge gap. There were not enough assessments for any of the 15 diseases to allow meta-analyses, whether these assessments dealt with companion animal disease risk or companion animal-associated human disease risk. Important method and technology gaps were the lack of harmonization in the case definitions used for a given disease and the lack of good diagnostics allowing pathogen identification to taxonomic levels that are meaningful for risk analysis. Molecular epidemiology studies on zoonotic pathogens, which included companion animals among the potential human risk factors, were not found, although such studies would provide good preliminary insights without requiring any tracing of people or any interviews. In addition to performing further risk studies that take into account these issues, there is a need for responsible pet ownership and continued education of professionals in companion animal zoonoses. Additional risk assessment studies should allow more targeted actions to reduce the risk of zoonotic diseases transferred via companion animals and provide information that will promote risk-awareness in healthy human–animal relationships.